Plant Growth Performance of Top Grafted Young Cacao at Various Elevations in Indonesia - Poleuleng, Andi Besse; Agusta, Herdhata; Yahya, Sudirman; Wachjar, Ade; Tjoa, Aiyen (Journal of Tropical Crop Science, 2020)
The purpose of this study was to evaluate the plant growth performance of top grafted young cacao cultivated in various elevations. This research was conducted from January-August 2019 in South Sulawesi and Central Sulawesi. A total of 54 plants were taken randomly from 6 locations with 3 altitudes (<300, 300-600, >600 meter above sea level, as.). The results showed that there was not significant different of plant height, stem circle, crown circle, the number of primary branches, the number of flowers, the length of horizontal and vertical roots in response to different elevations. However, the height of primary stem and leaves number of cacao from <300 m asl was significantly greater than those from either 300-600 m asl or > 600 m asl. The largest crown portion of actual biomass was found in the branches, then followed by the leaves and stem. While the highest actual root biomass was found at 10-20 cm soil depth.